The Effect of Self-Confidence Towards Public Speaking on Students of Islamic Education Study Program, Universitas Muhammadiyah Purwokerto - Pragita Bela Utari; Suwarti Suwarti; Dyah Astorini Wulandari; Itsna Nurrahma Mildaeni (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2022)
Students of the Islamic Religious Education Study Program should have good public speaking skills because students will become PAI teachers. Public speaking is the ability to speak in public using language that can be understood by listeners. Public speaking can be influenced by self-confidence, so students must have high self-confidence because it is intended that the ability to speak in front of many people goes well without feeling embarrassed, feeling awkward, and much more. This study aims to examine the effect of self-confidence on public speaking for students of UMP Islamic Education Study Program. This study used a simple random sampling technique as many as 181 students in the UMP Islamic Education Study Program. The data collection method uses a public speaking scale with a reliability of 0.941. Confidence scale with reliability of 0.902. The analytical technique used is simple linear regression analysis with SPSS version 25 program. The results of the study show that the F value is 626,992 with a t value of 25,040, the significance value (p) = 0.000 (p < 0.05), meaning that the proposed hypothesis can be accepted. with an Rsquare value of 0.778. This shows that self-confidence has an influence of 77.8% and 22.5% is influenced by other factors outside the study.